2005
DOI: 10.1007/s00232-005-0818-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ClC-2 Chloride Channels by a Peptide Component or Components of Scorpion Venom

Abstract: ClC chloride channels play essential roles in membrane excitability and maintenance of osmotic balance. Despite the recent crystallization of two bacterial ClC-like proteins, the gating mechanism for these channels remains unclear. In this study we tested scorpion venom for the presence of novel peptide inhibitors of ClC channels, which might be useful tools for dissecting the mechanisms underlying ClC channel gating. Recently, it has been shown that a peptide component of venom from the scorpion L. quinquestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Isolation and Proteomic Characterization of the Active ToxinWe recently showed that a peptide component of scorpion venom is capable of specifically inhibiting the ClC-2 chloride channel (18). To isolate the active species from venom, we used RP-HPLC to separate the components of Lqh pf-venom, which contains only components smaller than 10 kDa.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Isolation and Proteomic Characterization of the Active ToxinWe recently showed that a peptide component of scorpion venom is capable of specifically inhibiting the ClC-2 chloride channel (18). To isolate the active species from venom, we used RP-HPLC to separate the components of Lqh pf-venom, which contains only components smaller than 10 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…However, no peptide toxins have been isolated that inhibit a ClC channel, and only one toxin has been isolated that inhibits any Cl Ϫ channel of known molecular identity (17). We recently showed that venom from the scorpion Leiurus quinquestriatus hebraeus contains a peptide component that inhibits the ClC-2 chloride channel (18). Here, we report the isolation of this peptide toxin, its proteomic properties, and primary characteristics of the biophysical mechanism of inhibition.…”
Section: Clc Proteins Form a Family Of Voltage-gated CLmentioning
confidence: 99%
See 3 more Smart Citations